2023
DOI: 10.3389/fcvm.2023.1237043
|View full text |Cite
|
Sign up to set email alerts
|

Revolutionizing smartphone gyrocardiography for heart rate monitoring: overcoming clinical validation hurdles

Mohamed Elgendi,
Wenshan Wu,
Cuntai Guan
et al.

Abstract: Accurate heart rate (HR) measurement is crucial for optimal cardiac health, and while conventional methods such as electrocardiography and photoplethysmography are widely used for continuous daily monitoring, they may face practical limitations due to their dependence on external sensors and susceptibility to motion artifacts. In recent years, mechanocardiography (MCG)-based technologies, such as gyrocardiography (GCG) and seismocardiography (SCG), have emerged as promising alternatives to address these limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…For instance, Ramos-Castro et al demonstrated the viability of smartphones in recording cardiac activity, highlighting similarities with ECG signals despite certain limitations [6]. The study of beat-by-beat heart rate (HR) estimation, utilizing smartphone-based SCG primarily through acquiring angular rates via built-in gyroscopes, yielded positive results [7][8][9]. Furthermore, the potential of smartphone-derived SCG in identifying cardiac arrest scenarios was investigated, underscoring its future possibilities [10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ramos-Castro et al demonstrated the viability of smartphones in recording cardiac activity, highlighting similarities with ECG signals despite certain limitations [6]. The study of beat-by-beat heart rate (HR) estimation, utilizing smartphone-based SCG primarily through acquiring angular rates via built-in gyroscopes, yielded positive results [7][8][9]. Furthermore, the potential of smartphone-derived SCG in identifying cardiac arrest scenarios was investigated, underscoring its future possibilities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread prevalence of smartphones ( 14 ) has spurred innovations in smartphone-based heart rate (HR) estimation systems ( 15 , 16 ). Smartphone-based ECG systems often involve electrodes, which have been noted for causing skin irritation in some cases ( 17 ).…”
Section: Introductionmentioning
confidence: 99%